Accelerated aging signatures in subjects with schizophrenia and their unaffected siblings. (July 2021) - Rebouças, Diego Barreto; Sartori, Juliana Mastella; Librenza-Garcia, Diego; Rabelo-da-Ponte, Francisco Diego; Massuda, Raffael; Czepielewski, Leticia Sanguinetti; Passos, Ives Cavalcante; Gama, Clarissa Severino
Abstract: Schizophrenia (SZ) is a chronic debilitating disease. Subjects with SZ have significant shorter life expectancy. Growing evidence suggests that a process of pathological accelerated aging occurs in SZ, leading to early development of severe clinical diseases and worse morbimortality. Furthermore, unaffected relatives can share certain endophenotypes with subjects with SZ. We aim to characterize accelerated aging as a possible endophenotype of schizophrenia by using a machine learning (ML) model of peripheral biomarkers to accurately differentiate subjects with SZ (n = 35), their unaffected siblings (SB, n = 36) and healthy controls (HC, n = 47). We used a random forest algorithm that included biomarkers related to aging: eotaxins CCL-11 and CCL-24; the oxidative stress markers thiobarbituric acid-reactive substances (TBARS), protein carbonyl content (PCC), glutathione peroxidase (GPx); and telomere length (TL). The ML algorithm of biomarkers was able to distinguish individuals with SZ from HC with prediction accuracy of 79.7%, SZ from SB with 62.5% accuracy and SB from HC with 75.5% accuracy. These results support the hypothesis that a pathological accelerated aging might occur in SZ, and this pathological aging could be an endophenotype of the disease, once this profile was also observed in SB, suggesting that SB might suffer from an accelerated aging in some level. Highlights: High accuracy results point to the occurrence of accelerated aging in schizophrenia. Accelerated aging could be an endophenotype in schizophrenia. Unaffected siblings might display some biological changes seen in schizophrenia.